TINJAUAN YURIDIS PENERTIBAN PEDAGANG KAKI LIMA BERDASARKAN PERATURAN DAERAH NOMOR 11 TAHUN 2001 OLEH PEMERINTAH KOTA PEKANBARU TAHUN 2013 - Saddami, Arika; Haryono, Dodi; Ghafur, Abdul (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2014)
Street Vendors are business people who are doing business trade by means of movable or immovable, using urban infrastructure, social facilities, public facilities, land and buildings owned by the government and / or private temporary / not permanent. The presence of street vendors who occupy the fringes of town on the coastal road and in the coastal market is very disturbing traffic order, interference with pedestrian infrastructure, and congestion in the city of Pekanbaru. So the government made curbing street vendors in order to create a safe and clean environment. The purpose of this thesis, namely; First, hawkers Control Based on Regional Regulation No. 11 Year 2001 By the City of Pekanbaru In 2013, the Second, Obstacles encountered in Street Vendors Under Control Regional Regulation No. 11 Year 2001 By the City of Pekanbaru In 2013, the Third, efforts were made to overcoming Barriers in the Control of Street Vendors Based Regional Regulation No. 11 Year 2001 By Pekanbaru City Government in 2013.Keywords: Control - Street Vendors down- Town of Pekanbaru